2008
DOI: 10.1074/jbc.m800109200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-CD44 Interaction Activates Stem Cell Marker Nanog, Stat-3-mediated MDR1 Gene Expression, and Ankyrin-regulated Multidrug Efflux in Breast and Ovarian Tumor Cells

Abstract: Hyaluronan (HA) is a major glycosaminoglycan in the extracellular matrix whose expression is tightly linked to multidrug resistance and tumor progression. In this study we investigated HA-induced interaction between CD44 (a HA receptor) and Nanog (an embryonic stem cell transcription factor) in both human breast tumor cells (MCF-7 cells) and human ovarian tumor cells (SK-OV-3.ipl cells). Using a specific primer pair to amplify Nanog by reverse transcriptase-PCR, we detected the expression of Nanog transcript i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
394
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(408 citation statements)
references
References 97 publications
(171 reference statements)
8
394
0
6
Order By: Relevance
“…We have demonstrated for the first time that Nanog mRNA expression can be detected with high sensitivity and specificity in lung cancer tissues. In addition, experiments on siRNA revealed that the constitutive expression of Nanog in cancer cells maintains proliferation ability; this is consistent with the observation that the overexpression of the Nanog gene promotes tumour cell growth (11). With regard to the expression of Nanog in cancers, Ezeh et al showed that the Nanog protein is expressed in tissues that were obtained from 2 breast cancer patients (12).…”
Section: Discussionsupporting
confidence: 60%
“…We have demonstrated for the first time that Nanog mRNA expression can be detected with high sensitivity and specificity in lung cancer tissues. In addition, experiments on siRNA revealed that the constitutive expression of Nanog in cancer cells maintains proliferation ability; this is consistent with the observation that the overexpression of the Nanog gene promotes tumour cell growth (11). With regard to the expression of Nanog in cancers, Ezeh et al showed that the Nanog protein is expressed in tissues that were obtained from 2 breast cancer patients (12).…”
Section: Discussionsupporting
confidence: 60%
“…HA-CD44 interaction was proved to activate Nanog which is principally [20] involved in the stem cell maintenance and self-renewal in the ES cells [21,22]. The activation of CD44 through the PKCε phosphorylates Nanog, with or without the association of Stat3 regulates the expression of other pluripotent, tumorigenic and multidrug resistance genes [21]. Nanog has shown to regulate the expression of Sox2, Oct3/4, and Rex1, the prominent pluripotent transcription factors during embryonic stem cell pluripotency.…”
Section: Ha Induces the Expression Of Pluripotent Genesmentioning
confidence: 99%
“…These transcription factors are found to be over-expressed in several of the cancers and were used to identify cancer stem cell-like cells in glioblastoma [19]. HA-CD44 interaction was proved to activate Nanog which is principally [20] involved in the stem cell maintenance and self-renewal in the ES cells [21,22]. The activation of CD44 through the PKCε phosphorylates Nanog, with or without the association of Stat3 regulates the expression of other pluripotent, tumorigenic and multidrug resistance genes [21].…”
Section: Ha Induces the Expression Of Pluripotent Genesmentioning
confidence: 99%
“…Specifically, HA binding to CD44 is capable of stimulating MDR1 expression and drug resistance in breast tumour cells through ErbB2 signalling and PI3 kinase/Akt-related survival pathways (Misra et al, 2005). Bourguignon et al (2008) have recently shown that HA -CD44 interaction activates stem cell marker Nanog, Stat-3-mediated MDR1 gene expression and ankyrin-regulated multidrug efflux in breast and ovarian tumour cells. However, a direct link of phenotypes between drug resistance and invasion or metastasis in epithelial ovarian cancer (EOC) is still unclear.…”
mentioning
confidence: 99%